The acoustic voice quality index version 02.02 in the Finnish-speaking population. (2nd April 2020) - Kankare, Elina; Barsties V. Latoszek, Ben; Maryn, Youri; Asikainen, Marja; Rorarius, Eija; Vilpas, Sarkku; Ilomäki, Irma; Tyrmi, Jaana; Rantala, Leena; Laukkanen, Anne-Maria
Abstract: Background: The Acoustic Voice Quality Index (AVQI) is a multiparametric tool for objectively measuring the general acoustic characteristics of voice. The AVQI uses both sustained vowel and continuous speech in its analysis, and therefore, a validation is required for different languages. In the present study, validation was performed in the Finnish-speaking population. Methods: The study included 200 native Finnish-speaking participants of whom 115 were voice patients attending a phoniatric clinic, and the remaining 85 subjects participated in the study as healthy controls. Voice samples were recorded, and the auditory evaluation was performed by five speech therapists. An ordinal four-point interval scale was used to evaluate the degree of voice abnormality (Grade, G). Several statistical analyses were performed to test the validity and the diagnostic accuracy of the AVQI in the Finnish-speaking population. Results: The inter-rater reliability of four of the five raters was high enough to allow the use of G mean in the validation. There was a statistically significant correlation between the AVQI scores and the evaluation of overall perceptual voice quality ( r  = 0.74). Conclusions: The results confirmed the good discriminatory power of the AVQI in differentiating between normal and abnormal voice qualities. The AVQI 02.02 threshold value for dysphonia was 2.87 in the Finnish-speaking population.